ENVIRONMENTAL AWARENESS AND ENGLISH TEACHERS’ PROFESSIONAL IDENTITY: A MIXED-METHOD STUDY - Paschalis Kurniawan Sanjaya; Paulus Kuswandono (English Review: Journal of English Education, 2026)
Contemporary environmental challenges are increasingly demanding responses from the education sector. Teachers, as key educational agents, play an important role in fostering environmental awareness, and their professional identity may be influenced by how they perceive and respond to environmental issues. However, there is limited research that connects environmental awareness and teacher identity construction. Therefore, this research aims to examine how teachers’ environmental awareness influences their professional identity and their integration of environmental values in teaching. 80 English teachers participated in the questionnaire phase, and five teachers were selected for semi-structured interviews through purposive sampling. Descriptive statistics were used to analyze the quantitative data, while thematic analysis was applied to the qualitative data. The findings revealed that teachers’ environmental awareness influenced their moral self-positioning, pedagogical decision-making, and professional identity beyond language instruction. In addition, teachers integrated environmental values through implicit practices, such as modeling pro-environmental behaviors and daily classroom habituation, and through explicit practices, including the integration of environmental texts and experiences into learning materials and the use of teaching methods such as outdoor learning and environmental visualization. In conclusion, this study suggests that environmental awareness plays a significant role in shaping English teachers’ professional identity as educators.